Effects of labile carbon and phosphorus addition on N transformations with N‐ vs. non‐N‐fixing tree plantations. Issue 3 (24th March 2018) - Wang, Wenjuan; Li, Yingwen; Zhao, Qian; Liu, Xiaodong; Long, Fengling; Mo, Qifeng
Abstract: Phosphorus (P) is the primary factor limiting soil organic matter (SOM) decomposition and carbon (C) storage in the tropical P‐deficient plantations. However, the mineralization of SOM derived from N‐fixing and non‐N‐fixing plantations may respond differently to P addition within the laboratory‐ or field‐based incubation experiment. In this study, the effects of P addition (+P) combined with glucose (+Glu) on soil N mineralization within Eucalyptus urophylla (EU) and Acacia auriculiformis (AA) plantations were evaluated using a 60‐d laboratory aerobic incubation assay in subtropical China. The results showed that Glu addition significantly affected the net N mineralization and nitrification in both EU and AA plantations. In the 7th day incubation, +Glu treatment enhanced the N mineralization, whereas +Glu+P dramatically accelerated the N immobilization in EU plantation. However, +Glu+P treatment increased N mineralization while +Glu enhanced N immobilization in AA plantation, suggesting that P addition greatly affected the direction of N transformation within different plantations under the labile C input in the early stage of incubation. However, in the 15th day incubation, +Glu increased while +Glu+P greatly reduced the N immobilization in EU plantation. On the contrary, +Glu promoted while +Glu+P further accelerated the N immobilization in AA plantations, indicating that P addition had the contrasting effects on N immobilization within EU and AA plantations. After the 15th day incubation, Glu addition further facilitated the N immobilization in two plantations. Although +Glu increased the fungi and bacteria PLFA biomass, +Glu+P significantly increased F/B ratios, which may contribute to the direction and magnitude of N transformations in two plantations. However, in these two plantation forests with low soil P availability, single P addition would not significantly alter the N mineralization mediated by microbe in the laboratory incubation experiment without the labile C input. Therefore, the significant effects of P addition on the N mineralization or immobilization varied with the incubation stage and plantation types. We recommend that the P availability has profound implications on SOM decomposition and C sequestration in subtropical plantations.